Komunikasi Interpersonal Karyawan dalam Meningkatkan Minat Beli Pelanggan di K3Mart Adam Malik - Pakpahan, Sri Wulan; Matondang, Armansyah (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2025)
The increasingly competitive retail industry demands companies to enhance service quality as a strategy to retain customers. One crucial aspect of this service is employees’ interpersonal communication, which not only delivers product information but also builds trust and emotional comfort for customers. In this context, this study aims to examine the role of employees’ interpersonal communication in increasing customer purchase interest and to identify communication barriers encountered during the service process at K3MART Adam Malik. This research employs a qualitative approach with a descriptive method. Data were collected through participatory observation and in-depth interviews with five informants, consisting of three service employees and two regular customers. Data analysis was carried out through the stages of data reduction, data presentation, and thematic conclusion drawing. he results show that interpersonal communication characterized by friendliness, clarity, empathy, responsiveness, and solution orientation plays a significant role in enhancing customer purchase interest. Customers felt more comfortable and trusted the services provided, which led to improved purchasing decisions. However, several communication barriers were identified, including high workloads, language and cultural differences, lack of communication training, environmental noise, and uncooperative customer behavior. This research concludes that strengthening employees’ interpersonal communication skills and strategically managing communication barriers are crucial to enhancing service effectiveness and maintaining a competitive advantage in the retail sector.